Human Toll-like Receptor 8 (TLR8) Is an Important Sensor of Pyogenic Bacteria, and Is Attenuated by Cell Surface TLR Signaling - Moen, Siv H.; Ehrnström, Birgitta; Kojen, June F.; Yurchenko, Mariia; Beckwith, Kai S.; Afset, Jan E.; Damås, Jan K.; Hu, Zhenyi; Yin, Hang; Espevik, Terje; Stenvik, Jørgen (Frontiers in Immunology, 2019)
TLR8 is an endosomal sensor of RNA degradation products in human phagocytes, and is involved in the recognition of viral and bacterial pathogens. We previously showed that in human primary monocytes and monocyte derived macrophages, TLR8 senses entire Staphylococcus aureus and Streptococcus agalactiae (group B streptococcus, GBS), resulting in the activation of IRF5 and production of IFNβ, IL-12p70, and TNF. However, the quantitative and qualitative impact of TLR8 for the sensing of bacteria have remained unclear because selective inhibitors have been unavailable. Moreover, while we have shown that TLR2 activation attenuates TLR8-IRF5 signaling, the molecular mechanism of this crosstalk is unknown. We here used a recently developed chemical antagonist of TLR8 to determine its role in human primary monocytes challenged with S. aureus, GBS, Streptococcus pneumonia, Pseudomonas aeruginosa, and E. coli. The inhibitor completely blocked cytokine production in monocytes stimulated with TLR8-agonists, but not TLR2- and TLR4-agonists. Upon challenge with S. aureus, GBS, and S. pneumonia, the TLR8 inhibitor almost eliminated the production of IL-1β and IL-12p70, and it strongly reduced the release of IL-6, TNF, and IL-10. With P. aeruginosa infection, the TLR8 inhibitor impaired the production of IL-12p70 and IL-1β, while with E. coli infection the inhibitor had less effect that varied depending on the strain and conditions. Signaling via TLR2, TLR4, or TLR5, but not TLR8, rapidly eliminated IRAK-1 detection by immunoblotting due to IRAK-1 modifications during activation. Silencing of IRAK-1 reduced the induction of IFNβ and TNF by TLR8 activation, suggesting that IRAK-1 is required for TLR8-IRF5 signaling. The TLR-induced modifications of IRAK-1 also correlated closely with attenuation of TLR8-IRF5 activation, suggesting that sequestration and/or modification of Myddosome components by cell surface TLRs limit the function of TLR8. Accordingly, inhibition of CD14- and TLR4-activation during E. coli challenge increased the activation of IRF5 and the production of IL-1β and IL-12p70. We conclude that TLR8 is a dominating sensor of several species of pyogenic bacteria in human monocytes, while some bacteria attenuate TLR8-signaling via cell surface TLR- activation. Taken together, TLR8 appears as a more important sensor in the antibacterial defense system than previously known.